Prevalence, incidence, and risk of cancers in patients with acromegaly: review - Laszczak, Katarzyna; Niedobylski, Sylwiusz; Warchoł, Konrad; Dobosz, Maciej; Pachciński, Olaf (Journal of Education, Health and Sport, 2022)
Acromegaly is a relatively rare disease, with the incidence of 0.2 - 1.1 cases in 100 000 people per year. Increased secretion of growth hormone (GH) is the main pathomechanism. GH stimulates the liver to the insulin-like growth factor type 1 (IGF-1) production. It leads to the tissues overgrowth, facial changes, metabolic and cardiovascular comorbidities, such as diabetes, hyperthyroidism, or hypertension. The main aim of this review is to provide the most up to date knowledge about epidemiology and risk factors of neoplasms which occur more often in acromegaly, than in the general population. Some studies showed that substances from the IGF group – including IGF-1, have a cancerogenic effect on the cells. According to that fact, groups of acromegalic patients were examined in the search for cancers. Studies delivered that there is a higher chance of neoplasms in acromegalic patients. The most widely described cancers in the relation with this disease are: prostate cancer, breast cancer, thyroid cancer, and colon cancer. There are some neoplasms which have lesser number of studies, such as: renal cancer, neoplasms of the female reproductive system, haematological cancers as well as osteosarcoma. Cancers occurs more frequently in acromegalic patients and have a major impact on patients' life-span. Early detection as well as quick provision with the adequate treatment is highly necessary for extending patients’ lives.